Species Diversity of Freshwater Snails in Mae Lao Agricultural Basin (Chiang Rai, Thailand) and its Relationship with some Physio-chemical Parameters - Chantima, Kittichai; Thesarin, Chiraya (Journal of Mahanakorn Veterinary Medicine, 2018)
Mae Lao agricultural basin is located in the Mae Lao sub-river basin of Kok River basin, Chiang Rai province, Thailand. There is a scarcity of information on the diversity of freshwater snails in this area. Herein, the aim of this study was to assessing the freshwater snail diversity and the abundance in relation to the physio-chemical properties in different watercourse. Physio-chemical properties and snails were sampled in 10 sites in Mae Lao district to characterize the snail habitats. Species richness, Shannon’s diversity and evenness indices were employed to describe snail diversity and diversity across the habitat types. Statistical analyses were conducted to examine the extent to which the physio-chemical properties and abundance of snails. Among 3,725 collected snails, 12 snail species namely Bithynia funiculata, B. siamensis goniomphalos, B. s. siamensis, Clea helena, Trochotaia trochoides, Filopaludina doliaris, F. martensi martensi, F. sumatrensis polygramma, Lymnaea auricularia, Melanoides tuberculata, Pomacea canaliculata and Corbicula sp. were identified. 9 out of these 12 snail species are of medical and veterinary importance. B. s. siamensis and M. tuberculata were the most enumeration of snail species. Analysis of the data revealed that the physio-chemical properties no significant difference across the stream and rice paddy habitats. However, freshwater snail abundance was significant correlated with dissolved oxygen and pH in stream habitat (p<0.05). In addition, different habitats had different species diversity and snail abundance with high snail abundance at stream habitats. The present study is the first research on the freshwater snail fauna in Mae Lao agricultural basin and all snail species were recorded for the first time from this area.